Coral Larvae Dispersal Following Observed Spawning Events at Tunda Island, Western Java, Indonesia - Fakhrurrozi; Yusuf, Syafyudin; R. Zedta, Raymon; Mujiyanto; R.A. Putri, Masayu; Gunadharma Gautama, Budhi; Idris; Rachmawati, Rita (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abtsract   Highlight Research 1. Integration of direct coral spawning observations with larval dispersal modeling at Tunda Island. 2. High local retention rates are predominantly driven by larval pre-competent periods. 3. Larval export patterns indicate significant connectivity toward existing Marine Protected Areas (MPAs) in Northern Java. 4. Emphasizes the critical need for integrated management of non-protected sites to sustain regional reef networks.   Abstract Dispersal patterns varied significantly among the days of the spawning event. Event in 18 March showed particle distribution that favored local retention, whereas others event in 13 and 14 March showed a more export-oriented. Most particle remained within 50 km of the source reef, but a fraction dispersed up to 230 km and remained active, indicating potential for regional connectivity. Overall, most stranded particles occurring during the pre-competent phase, suggesting a temporal mismatch between biological settlement and reef contact. Spatial aggregation data show Tunda Island may function as larval source for multiple reef systems in Northern Java, such as Seribu Islands, Biawak Island, Ujung Kulon, even Karimunjawa Islands. These findings emphasize the importance of integrating empirical spawning observation with biophysical modeling to capture event-scale variability in connectivity and underscore the ecological significance of reef outside formally designated marine protected area in sustaining regional reef networks.